Evaluate the Climatic Conditions for the Al-Najaf –Ain-Al-Tamur Area (Middle of Iraq) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study includes determining the climatic conditions of the study area and the nature of the reservoirs in the region with the determination of the flow direction of the aquifer. The meteorological data for the Karbala station for the period 1976-2016 showed that the values of the monthly rates of temperature, precipitation, evaporation, relative humidity, wind speed and Sunshine duration are (24.19 C◦), (95.5 mm), (2828.6mm), (46.75%), (2.76 m/sec), and (8.61 h/day) respectively. Thorenthwait method was used to calculate the values of Potential Evapotranspiration (PE) then determine the annual value of Water Surplus( WS) and  Water Deficit (WD) which equal( 28.11mm) and (941.94mm) respectively. Mean monthly water surplus for the period (1976-2016) was recorded about (9.36mm) in December, (13.11mm) in January and (5.64mm) in February of the whole amount of Rainfall and Equal to (29.34mm) of the total rainfall. The flow net map is shown by mainly that the groundwater flow in the area, it is from the northwestern parts towards the Eastern and southeastern parts.